The impact of SnO2 photoelectrode’s thickness on photovoltaic properties of the solar cell FTO:SnO2:PTB7-TH:ITIC/Mo/Ag - Aimukhanov, A.K.; Seisembekova, T.E.; Zeinidenov, A.K.; Kambar, D.S. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The paper reports the results of a study of the morphological, optical and electrophysical parameters of SnO2 films. SnO2 films are applied by spin-coating at different revolutions of the centrifuge. The topography of the surface and the thickness of the SnO2 films are studied using an atomic force microscope. The current-voltage characteristics of solar cells are measured. The optical properties with different thicknesses of SnO2 films are also investigated. It is shown that an increase in the rotation speed of the substrate leads to a decrease in the surface roughness of the SnO2 films. It is found that changes in the morphology of SnO2 films contribute to the rapid transport of injected holes to the external electrode and reduce the probability of reverse recombina-tion. Cells with an electron transport layer of SnO2 at 2000 revolutions showed a low efficiency of 0.17%. With a decrease in the thickness of the SnO2 films to a value of 62 nm, there is an increase in the value of the short-circuit current by 2.3 times and a change in the no-load voltage by 1.12 times.
SnO фотоэлектроды қалыңдығының FTO:SnO:PTB7-TH:ITIC/Mo/Ag күн ұяшығының фотоэлектрлік параметрлеріне әсері
Влияние толщины фотоэлектрода SnO на фотоэлектрические параметры солнечной ячейки FTO:SnO:PTB7-TH:ITIC/Mo/Ag
Keywords: Tin(II) oxide (SnO2) surface morphology; optical and impedance spectroscopy